Transculturality of the Alps: The Role of Image and Sound in a European “Multiple Bergfilm” of the 1930s (Cinéma & Cie. Film and Media Studies Journal, 2023)
The discovery of the Alps in the specific genre of the mountain film was originally a German answer to the Westerns from the USA in the late 1920s. This brought a number of important personalities such as Fanck, Riefenstahl and Trenker onto the German film market, though the genre developed in different ways in other contexts, too. The mountain film Der Sohn der weißen Berge / Les Chevaliers de la Montagne by Trenker and Bonnard was coproduced as a German-French multiple version (MV) in 1930 and represents the beginning of a longer series of ‘multiple’ coproductions by Trenker. During the generalization of sound, MVs are meant to create the ‘same’ film for each country interested in it. In order to make the versions successful in their contexts, each of them is shaped according to early audio-visual techniques and adapting elements such as cast, fictional nationalities, music, dialogues or gestures. This article aims to approach the two MVs from a comparative, transcultural perspective in order to highlight their specificities. The aim is to investigate the transcultural character of the Alps arguing that, due to their semantic openness, the Alps provide an ideal setting for transcultural communication and for the nationalization process essential to the MVs. As a territory at the crossroad of several countries and cultures, the Alpine environment proves through Der Sohn der weißen Berge / Les Chevaliers de la Montagne to be a privileged territory for multiplecinematic cultural transfers that contribute to the establishment of European cinema.
Keywords: Mountain Films; Multiple Versions; Luis Trenker; Transculturality; Alps